Theoretical and experimental analysis of dynamic plate heat exchanger: Non-retrofit configuration. (25th January 2016) - Ebrahimzadeh, Edris; Wilding, Paul; Frankman, David; Fazlollahi, Farhad; Baxter, Larry L.
Highlights: Eliminating the heat exchanger performance decrease subject to transient flow rates. Mathematical modeling of plate heat exchanger using the orthogonal collocation method. Rapid system response through transient flow rates. Non-retrofit configuration of heat exchangers. Abstract: This document theoretically and experimentally describes a dynamic plate heat exchanger, a device that can decrease or eliminate heat exchanger performance and efficiency losses associated with transient changes in flow rates and other sources of imbalance. Heat exchanger constraints may represent the most restrictive transient response constraints in a process and thereby compromise the agility and responsiveness of processes. These constraints include thermal stresses, expansion, or temperature changes in the devices or their near neighbors in the flow process. The proposed design is capable of leveling varying conditions such that the exit temperatures remain fixed despite the changes in inlet conditions. Experimental and theoretical results indicate that the proposed design can respond to changes in process flow rates with a near-zero time constant.